Pengaruh Literasi Keuangan dan Financial Technology terhadap Inklusi Keuangan pada UMKM Kelurahan Yosodadi Kecamatan Metro Timur - Rahmadanti, Silvi Wahyu; Zanaria, Yulita; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of financial literacy and fintech on financial inclusion in SMEs in Yosodadi Village, Metro Timur District. The type of research used in this research is quantitative research with an associative approach. Data analysis was carried out by testing instruments, classical assumptions and testing hypotheses. The results showed that financial literacy (X1) had a significant effect on financial inclusion in UMKM Yosodadi Village. When a person has a high level of understanding of financial concepts, the higher the level of one's financial inclusion. Financial Technology (X2) has a significant effect on financial inclusion in Yosodadi Village SMEs. The higher use of Fintech will support the level of financial inclusion. Where the availability of access and financial services will be wider and easier to reach